The Migration of the Eurasian Woodcock (Scolopax rusticola L.) in the Carpathian Basin at the Turn of the 19–20th Centuries - László Bozó; István Fekete; Attila Bende (Birds)
In the present study, 7344 spring observations of a short-distance migratory species, the Eurasian Woodcock, from the Carpathian Basin between 1894 and 1926 were used to investigate the timing of the species’ migration and how different environmental factors influenced it. We used a generalized additive model (GAM) to explore migratory patterns by using environmental and geographical variables. In years when the weather was colder and snowier, the birds migrated weeks later than in years with milder weather. This may be due to the availability of earthworms, which are the most important food for the species. In areas at lower altitudes, migration occurred earlier than in mountainous areas, which may also be due to the different weather. Furthermore, a two week difference was observed between the south-western and north-eastern parts of the Carpathian Basin. This difference is still present nowadays, but the timing of migration has shifted earlier than in the past, probably due to climate change. It would also be important to compare the historical data with recent data to gain a better understanding of the effects of climate change on the migration of the Eurasian Woodcock.